Integrating Digital Literacy into Curriculum Design a Framework for 21st Century Learning - Jordan, Afrind; Julianto, Agil; Firmansyah, Moch Ariya (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
In the modern digital era, integrating digital literacy into curriculum design is critical to preparing students for 21st-century challenges. Digital literacy encompasses more than technical skills; it includes intellectual competence, ethical awareness, and adaptive behavior necessary for modern personal and professional environments. This study explores strategies for embedding digital literacy into educational frameworks, leveraging methodologies like digital storytelling and Inquiry-Based Learning (IBL). These approaches enable active, student-centered learning while fostering critical thinking, creativity, collaboration, and communication. Key findings highlight that technology, when properly implemented, enhances engagement and learning effectiveness by tailoring material to individual needs and encouraging experiential exploration. The research also underscores the necessity for institutional support, including teacher training, infrastructure, and equitable access to technology to minimize the digital divide. Despite its potential, challenges remain, such as resistance to educational change and concerns over student data privacy. This study contributes by proposing the TPACK framework, which integrates content knowledge, pedagogy, and technology, as a guide for comprehensive digital literacy integration. Future research should examine the long-term impacts of these practices on educational outcomes and refine tools and strategies for teacher development and technology application in classrooms.